Nonlinear Dynamic Characteristics of Fixed-Axis Gear Wear in Multistage Gear Transmission Systems - Xin Wang (Shock and Vibration)
With the increasing service life of a gear transmission system, the gear teeth become constantly worn and the gear clearance increases. The increase in the clearance will produce a series of nonlinear changes that change the stability of the system and can even cause the loss of stability. In this paper, dimensionless dynamic equations of a multistage gear transmission system that contains a two-stage fixed-axis gear and a one-stage planetary gear were derived. The wear fault was simulated by changes in the gear clearance. System bifurcation diagrams with an increase in the clearance were studied. The motion state and transition process of the multistage gear transmission system with a wear fault were studied using the Poincaré section. The change in the spectrum characteristics with an increase in the clearance was analyzed. The frequency spectrum characteristics of the wear fault were discovered. The vibration mechanism and a fault wear diagnosis method in a multistage gear transmission system were obtained.